Preparation method of samarium-doped hafnium oxide ferroelectric film with high remanent polarization value
The preparation of samarium-doped hafnium dioxide ferroelectric films by chemical solution deposition method solves the problems of large sol particles and slow deposition speed in the preparation process of HfO2-based films in the prior art, and achieves the effect of high residual polarization value and good film formation uniformity.
Patent Information
- Application Number
- CN202510037833.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-10
AI Technical Summary
In the preparation of HfO2-based ferroelectric films, the prior art problems such as large sol particles, slow deposition speed, easy formation of holes and cracks by heating, poor process repeatability, and low residual polarization value.
A samarium-doped hafnium dioxide ferroelectric film was prepared by chemical solution deposition. By controlling the film thickness, the content of doped elements, the annealing process and other process parameters, a film with a stable existence of single-climbed phase, cubic phase or its mixed phase was obtained.
The ferroelectric properties of the film are improved, the residual polarization value is enhanced, the film formation uniformity and process repeatability are improved, and the equipment requirements and production costs are reduced.
Smart Images

Figure CN119789781A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ferroelectric material preparation, and in particular relates to a method for preparing a samarium-doped hafnium dioxide ferroelectric film with a high remanent polarization value. Background Art
[0002] In recent years, with the rapid development of the microelectronics industry, electronic devices have become an indispensable part of people's daily lives. Among them, storage devices, as data carriers, need to perform complex processing on large amounts of data in a short period of time. Therefore, it is urgent to manufacture a new type of device with smaller size, faster read and write speed, and low power consumption.
[0003] As a new type of non-volatile storage device, ferroelectric memory has attracted extensive attention in the field of microelectronics due to its advantages such as low power consumption, fast response, repeatable read and write, and high stability storage. Compared with traditional ferroelectric materials, HfO 2 Ferroelectric thin film materials are highly compatible with complementary metal-oxide-semiconductor (CMOS) processes, so studying and improving their ferroelectric properties will help promote the further development of ferroelectric memory.
[0004] Existing studies have shown that HfO 2 Under standard pressure, it mainly exists in the following three phases: 1) At room temperature, the crystal exists in the low-temperature monoclinic phase (m phase, space group: P2 1 / c) exists stably; 2) above 2050 K, the crystal is in the medium-temperature tetragonal phase (t phase, space group: P4 2 / nmc); 3) Above 2803 K, the crystal exists in high temperature cubic phase (c phase, space group: )exist.
[0005] The orthorhombic phase (o-phase) with non-centrosymmetric polarity is considered to be the source of the ferroelectricity of hafnium oxide-based films, but this crystal phase is unstable at room temperature. Currently, the main ways to maintain the stability of the o-phase include doping, mechanical strain engineering, surface / interface / grain boundary energy effects and oxygen vacancy regulation. Among them, doping can induce phase transition and regulate the oxygen vacancy concentration to improve the ferroelectric properties of hafnium oxide-based films.
[0006] There are literatures in the prior art that have studied the ferroelectricity of hafnium oxide films doped with different elements. The results show that trivalent cation dopants are more conducive to the ferroelectricity of hafnium-based films than divalent cation dopants, and dopants with larger ion radius are more conducive to the formation of orthorhombic phases in hafnium-based films than dopants with smaller ion radius. Therefore, most of the doping elements in hafnium-based films with excellent ferroelectric properties are lanthanide elements and metal elements with large ion radius.
[0007] At present, the preparation of HfO 2There are many methods for preparing HfO thin films, which can be roughly divided into atomic layer deposition (ALD), physical vapor deposition (PVD), chemical vapor deposition (CVD), chemical solution deposition (CSD), etc. The traditional sol-gel method is to prepare HfO 2 Thin films have the disadvantages of large sol particles, slow deposition speed, easy formation of holes and cracks when heated, poor process repeatability, and low residual polarization value. Chemical solution deposition (CSD) is a technology that deposits materials in a precursor solution on the surface of a substrate through a chemical reaction to form a thin film. The chemical solution deposition method has the advantages of simple and easy process, strong controllability, strong environmental friendliness and sustainability, and good film quality and uniformity. Therefore, it is of great significance to provide a preparation method for hafnium dioxide ferroelectric thin films using a chemical solution deposition method and its application. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value.
[0009] The technical solution of the present invention is specifically: a method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value, comprising the following steps: S1: preparing a precursor solution; specifically comprising the following sub-steps: S11: adding hafnium salt to a solvent and stirring until all of it is dissolved; S12: adding samarium salt and stirring until a clear solution is obtained; S13: Aging in the dark to obtain a clear light yellow samarium-doped hafnium dioxide precursor solution; S2: cleaning the substrate; S3: coating and drying; specifically, coating the precursor solution obtained in S1 on the substrate cleaned in S2, removing surface impurities before coating; placing the substrate on a glue baking machine for drying after each coating, transferring the heated and dried substrate to a heating table for pyrolysis, cooling the dried and pyrolyzed film, and then coating the next layer; repeating the above steps until the desired film thickness is prepared; S4: Preheating the film: placing the film obtained in S3 in an annealing furnace filled with protective gas for pre-annealing, then annealing, and cooling to room temperature in the furnace to prepare a samarium-doped hafnium dioxide ferroelectric film; S5: Plate the samarium-doped hafnium dioxide ferroelectric thin film prepared in S4 onto an electrode.
[0010] Furthermore, the hafnium salt added in S11 is C 20 H 28 HkDJ8 ; The samarium salt added in S12 is Sm(NO 3 ) 3 •6H 2 O; the molar percentage of samarium is in the range of 1 to 15 mol%.
[0011] Furthermore, the concentration range of the samarium-doped hafnium dioxide precursor solution in S13 is 0.1-0.2 mol / L, preferably 0.1-0.15 mol / L.
[0012] Further, the molar percentage of samarium ranges from 1 to 5 mol%, preferably from 1.25 to 3.75 mol%, and in the precursor solution, the molar percentage is calculated based on the sum of the molar percentage of samarium and the molar percentage of hafnium being 100 mol%.
[0013] Furthermore, the solvent in S11 is a mixed solution of acetic acid solution and acetylacetone solution, wherein the volume ratio of acetic acid solution to acetylacetone solution is in the range of 1-2, and the pH of acetylacetone solution is adjusted to 3-5; when adding the solvent, the acetic acid solution should be added first, and after stirring, observe whether the solute is dissolved in the solvent, and then add the acetylacetone solution as a stabilizer.
[0014] Furthermore, the substrate in S2 is Pt(111) / TiN / SiO 2 / Si(100) substrate; the surface pretreatment method of the dried substrate is to use an ultraviolet ozone cleaning machine for treatment.
[0015] Furthermore, in S2, an ultrasonic cleaning method is used to clean the substrate. After each ultrasonic cleaning, water is used to rinse to remove impurities and dirt on the surface of the substrate. The substrate is soaked in anhydrous ethanol and dried before use. The dried substrate is then surface pretreated. When ultrasonic cleaning is performed, water ultrasonic cleaning is used for 4 to 6 min, anhydrous ethanol ultrasonic cleaning is used for 5 to 15 min, water ultrasonic cleaning is used for 4 to 6 min, acetone ultrasonic cleaning is used for 5 to 15 min, and water ultrasonic cleaning is used for 4 to 6 min.
[0016] Furthermore, after each layer is coated in S3, the substrate needs to be placed on a 150~180 ℃ glue baking machine to dry for 3~5 minutes, and then the heated and dried substrate is transferred to a heating table at 300 ℃~400 ℃ for pyrolysis for 5~10 minutes, and then the dried and pyrolyzed film is cooled for 3~5 minutes before the next layer is coated.
[0017] Furthermore, the coating method in S3 is spin coating, specifically, low-speed spin coating and high-speed spin coating are performed in sequence; the speed of low-speed spin coating is 300~600 r / min, and the time of low-speed spin coating is 10~20 s; the speed of high-speed spin coating is 3000~5000 r / min, and the time of high-speed spin coating is 25~45 s; the coating and drying steps in S3 can be repeated multiple times according to the film thickness requirements to control the thickness of the single-layer samarium-doped hafnium dioxide film to be 10~20 nm.
[0018] Furthermore, the process parameters of annealing in S4 are: heating from room temperature to 180~300 ℃ at a heating rate of 3~10 ℃ / s, then heating to 400~950 ℃ at a heating rate of 10~40 ℃ / s, keeping warm for 100~600 s, and cooling to room temperature with the furnace; the gas in the furnace is one or more of oxygen, nitrogen, argon or air.
[0019] Compared with the prior art, the present invention has the following advantages: 1. The present invention adopts a chemical solution method to prepare a samarium-doped hafnium dioxide precursor solution. By controlling the process parameters such as film thickness, the content of doping elements, and annealing process, a samarium-doped hafnium dioxide ferroelectric film in a stable monoclinic phase, cubic phase, or a mixed phase thereof can be obtained at room temperature, thereby improving the initial intrinsic ferroelectric properties of the film and the lower ferroelectric properties induced under an external electric field.
[0020] 2. The film prepared by the method of the present invention has a precisely controllable thickness, good film uniformity, simple operation, and flexible and controllable content of doping elements. The concentration of the doping elements can be precisely controlled, and there is no need to perform quantitative analysis on the composition of the film after deposition. At the same time, the equipment requirements are simple, energy-saving and environmentally friendly, low cost and high efficiency, high process repeatability, and easy to realize industrial production.
[0021] 3. The present invention can make the prepared film have a larger residual polarization value and a lower coercive field by controlling the amount of each source and the pH value of the precursor solution, the number of coatings, and the annealing process.
[0022] 4. The samarium-doped hafnium dioxide film prepared by the present invention is dense and uniform, and has a small leakage current.
[0023] 5. The present invention can control the film thickness by adjusting the amount of solvent added to the colloid, the number of film deposition layers, spin coating process parameters, etc., and the operation is simple and controllable.
[0024] 6. The present invention does not require advanced and expensive coating equipment, nor does it require a harsh operating environment. Experimental operations can be completed at room temperature. The equipment and environmental requirements are simple, and it is suitable for mass production with low equipment cost.
[0025] 7. Compared with the traditional sol-gel method for preparing HfO2 The film can avoid the shortcomings of large sol particles, slow deposition speed, easy formation of holes and cracks when heated, and poor process repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the GIXRD pattern of the sample with a samarium doping concentration of 2.5 mol% in Example 1.
[0027] Figure 2 The hysteresis loop and transient current-electric field curve of the sample with a samarium doping concentration of 2.5 mol% in Example 1.
[0028] Figure 3 This is the leakage current diagram of the sample with a samarium doping concentration of 2.5 mol% in Example 1.
[0029] Figure 4 1 and 2. The hysteresis loop and transient current-electric field curve of the sample with a samarium doping concentration of 1.25 mol% in Example 2.
[0030] Figure 5 The hysteresis loop and transient current-electric field curve of the sample with a samarium doping concentration of 3.75 mol% in Example 3. DETAILED DESCRIPTION
[0031] In order to make the process and purpose of the present invention clearer, the following Figure 1-5 And specific embodiments are provided to further illustrate the steps of the present invention in more detail. Embodiment 1
[0032] A method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value, comprising preparing a samarium-doped hafnium dioxide precursor solution having a samarium doping molar percentage of 2.5 mol%, and comprising the following steps: S1: preparing a precursor solution; specifically comprising the following sub-steps: S11: adding a hafnium salt to a solvent and stirring until it is completely dissolved; the added hafnium salt is C 20 H 28 HkDJ 8 ; S12: Add samarium salt and stir for more than 2 hours until a clear solution is obtained; the samarium salt added is Sm(NO 3 ) 3 •6H 2 O.
[0033] S11 and S21 are specifically as follows: weigh appropriate amounts of hafnium acetylacetonate and samarium nitrate hexahydrate and dissolve them in 3 ml of acetic acid to prepare a samarium-doped hafnium dioxide precursor solution, wherein the concentration of the hafnium dioxide precursor solution is 0.1 mol / L, wherein the doping molar percentage of samarium is 2.5 mol%, that is, the molar concentration of samarium is 0.0025 mol / L. After all the solutes are dissolved, add an appropriate amount of acetylacetone solution, the volume ratio of the acetic acid solution to the acetylacetone solution is 1.5, adjust the pH value to 4 and make it have stable solution chemical properties, and after obtaining a light yellow clear solution, transfer the solution to a magnetic stirrer at 25°C and stir for 2 hours until a clear solution is obtained.
[0034] S13: After obtaining a clear solution, ageing in a dark environment for more than 72 hours to obtain a clear light yellow samarium-doped hafnium dioxide precursor solution.
[0035] S2: Clean the substrate. Pt(111) / TiN / SiO 2 / Si(100) substrate, the surface pretreatment method of the dried substrate is to use an ultraviolet ozone cleaning machine to treat for 3 minutes.
[0036] When cleaning the substrate, first use deionized water for ultrasonic cleaning for 5 min, then use anhydrous ethanol for ultrasonic cleaning for 10 min, continue to use deionized water for ultrasonic cleaning for 5 min, then use acetone for ultrasonic cleaning for 10 min, and then use deionized water for ultrasonic cleaning for 5 min.
[0037] After each step of ultrasonic cleaning, rinse with a large amount of deionized water to remove impurities and dirt on the surface of the substrate to prevent stains from adhering to the surface of the substrate. Soak the substrate in anhydrous ethanol and dry it before use. Then pre-treat the surface of the dried substrate to increase the adsorption of the substrate surface to the precursor solution.
[0038] S3: coating and drying treatment; specifically, coating the precursor solution obtained in S1 on the substrate cleaned in S2, using a balloon to blow away surface impurities before coating, placing the substrate on a 165°C glue baking machine for drying for 4 min after each coating, then transferring the heated and dried substrate to a 350°C heating table for pyrolysis for 8 min, then cooling the dried and pyrolyzed film for 4 min, and then coating the next layer; repeating the above steps until the desired film thickness is prepared.
[0039] The coating process uses a spin coating process, and low-speed spin coating and high-speed spin coating are performed in sequence: Pt(111) / TiN / SiO 2 / Si(100) substrate is placed on a spin coater, and the precursor solution is dripped onto the surface of the substrate until it is fully covered. Then, it is first spun at a low speed of 500 r / min for 15 s, and then spun at a high speed of 4000 r / min for 40 s. Subsequently, it is placed in a glue baking machine and heated at 165 ° C for 4 min and 350 ° C for 8 min. The coating and drying steps can be repeated multiple times according to the film thickness requirements. The thickness of the single-layer samarium-doped hafnium dioxide film needs to be controlled to be 10-20 nm. In this embodiment, the above operation is repeated, and 4 layers are spin-coated to obtain a samarium-doped hafnium dioxide film with a film thickness of 66 nm.
[0040] S4: Preheating the film: Place the film obtained in S3 in an annealing furnace filled with protective gas for pre-annealing, then anneal, and cool to room temperature in the furnace to prepare a samarium-doped hafnium dioxide ferroelectric film. The specific method of annealing is: Place the substrate coated with the film in S3 in an annealing furnace for annealing. The annealing includes a pre-annealing process and a formal annealing process. The protective atmosphere is oxygen. The annealing process parameters are set as follows: During pre-annealing, slowly heat from room temperature to 200 °C at a heating rate of 5 °C / s, keep for 3 min, and then heat to 300 °C at a heating rate of 10 °C / s, and keep for 3 min. Entering the formal annealing, during the formal annealing, the temperature is heated to 500 °C at a heating rate of 20 °C / s, maintained for 5 min, and finally heated to 800 °C at a heating rate of 40 °C / s, maintained for 180 s, and then cooled to room temperature with the furnace before being taken out. The gas in the furnace is one or more of oxygen, nitrogen, argon or air. In this embodiment, the gas in the furnace is oxygen.
[0041] S5: The samarium-doped hafnium dioxide ferroelectric thin film prepared in S4 is plated with an electrode, wherein the electrode is an Au electrode.
[0042] The prepared samarium-doped hafnium dioxide ferroelectric film was integrated into the capacitor structure, and its electrical performance was tested using a ferroelectric analyzer and a semiconductor measuring instrument. The capacitor structure was metal-on-Sm-HfO 2 Ferroelectric thin film-metal (MIM) structure, and finally the ferroelectric performance is tested.
[0043] The sample is mainly in orthogonal phase, and its residual polarization value is 12.59~16.26 μC / cm 2 , the coercive field range is 0.9-1.2 MV / cm, the GIXRD spectrum, hysteresis loop, transient current-field curve and leakage current of the samples are shown as follows Figure 1 , Figure 2 and Figure 3 shown. Embodiment 2
[0044] A method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value, comprising preparing a samarium-doped hafnium dioxide precursor solution having a samarium doping molar percentage of 1.25 mol%, and comprising the following steps: S1: preparing a precursor solution; specifically comprising the following sub-steps: S11: adding a hafnium salt to a solvent and stirring until it is completely dissolved; the added hafnium salt is C 20 H 28 HkDJ 8 ; S12: Add samarium salt and stir for more than 2 hours until a clear solution is obtained; the samarium salt added is Sm(NO 3 ) 3 •6H 2 O.
[0045] S11 and S21 are specifically as follows: weigh appropriate amounts of hafnium acetylacetonate and samarium nitrate hexahydrate and dissolve them in 3 ml of acetic acid to prepare a samarium-doped hafnium dioxide precursor solution. The concentration range of the precursor solution is 0.15 mol / L, wherein the doping molar percentage of samarium is 1.25 mol%. After all the solutes are dissolved, add an appropriate amount of acetylacetone solution, the volume ratio of the acetic acid solution to the acetylacetone solution is 1, adjust the pH value to 3 and make it have stable solution chemical properties, and after obtaining a light yellow clear solution, transfer the solution to a magnetic stirrer at 25°C and stir for 2 hours until a clear solution is obtained.
[0046] S13: After obtaining a clear solution, ageing in a dark environment for more than 72 hours to obtain a clear light yellow samarium-doped hafnium dioxide precursor solution.
[0047] S2: Clean the substrate. Pt(111) / TiN / SiO 2 / Si(100) substrate, the surface pretreatment method of the dried substrate is to use an ultraviolet ozone cleaning machine for 1 minute.
[0048] When cleaning the substrate, first use deionized water for ultrasonic cleaning for 4 minutes, then use anhydrous ethanol for ultrasonic cleaning for 5 minutes, continue to use deionized water for ultrasonic cleaning for 4 minutes, then use acetone for ultrasonic cleaning for 5 minutes, and then use deionized water for ultrasonic cleaning for 4 minutes.
[0049] After each step of ultrasonic cleaning, rinse with a large amount of deionized water to remove impurities and dirt on the surface of the substrate to prevent stains from adhering to the surface of the substrate. Soak the substrate in anhydrous ethanol and dry it before use. Then pre-treat the surface of the dried substrate to increase the adsorption of the substrate surface to the precursor solution.
[0050] S3: coating and drying treatment; specifically, coating the precursor solution obtained in S1 on the substrate cleaned in S2, using a balloon to blow away surface impurities before coating, placing the substrate on a 150°C glue baking machine for drying for 3 min after each coating, then transferring the heated and dried substrate to a 300°C heating table for pyrolysis for 5 min, then cooling the dried and pyrolyzed film for 3 min, and then coating the next layer; repeating the above steps until the desired film thickness is prepared.
[0051] The coating process uses a spin coating process, and low-speed spin coating and high-speed spin coating are performed in sequence: Pt(111) / TiN / SiO 2 / Si(100) substrate is placed on a spin coater, and the precursor solution is dripped onto the surface of the substrate until it is fully covered. Then, it is first spun at a low speed of 300 r / min for 10 s, and then spun at a high speed of 3000 r / min for 25 s. Subsequently, it is placed in a glue baking machine and heated at 150 ° C for 3 min and 300 ° C for 5 min. The coating and drying steps can be repeated multiple times according to the film thickness requirements. The thickness of the single-layer samarium-doped hafnium dioxide film needs to be controlled to be 10-20 nm. In this embodiment, the above operation is repeated, and 4 layers are spin-coated to obtain a samarium-doped hafnium dioxide film with a film thickness of 40 nm.
[0052] S4: Preheating the film: Place the film obtained in S3 in an annealing furnace filled with protective gas for pre-annealing, then anneal, and cool to room temperature in the furnace to prepare a samarium-doped hafnium dioxide ferroelectric film. The specific method of annealing is: Place the substrate coated with the film in S3 in an annealing furnace for annealing. The annealing includes a pre-annealing process and a formal annealing process. The protective atmosphere is oxygen. The annealing process parameters are set as follows: During pre-annealing, slowly heat from room temperature to 180 °C at a heating rate of 3 °C / s, keep for 3 min, and then heat to 300 °C at a heating rate of 10 °C / s, and keep for 3 min. Entering the formal annealing, during the formal annealing, the temperature is heated to 400 ° C at a heating rate of 10 ° C / s, maintained for 100 seconds, and finally heated to 700 ° C at a heating rate of 30 ° C / s, kept warm for 200 seconds, and then cooled to room temperature with the furnace before being taken out. The gas in the furnace is one or more of oxygen, nitrogen, argon or air. In this embodiment, the gas in the furnace is argon.
[0053] S5: The samarium-doped hafnium dioxide ferroelectric thin film prepared in S4 is plated with an electrode, wherein the electrode is an Au electrode.
[0054] Prepare a samarium-doped hafnium dioxide precursor solution with a samarium doping molar percentage of 1.25 mol% to obtain metal-Sm:HfO 2Thin-film-metal (MIM) capacitors are tested for their ferroelectric properties using a ferroelectric analyzer and a semiconductor tester.
[0055] The sample was found to be a mixture of monoclinic and orthorhombic phases, with a residual polarization range of 8.47 to 12.74 μC / cm 2 , the coercive field range is 1.0-1.5 MV / cm, the sample hysteresis loop and transient current-electric field curve are as follows Figure 4 shown. Embodiment 3
[0056] A method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value, comprising preparing a samarium-doped hafnium dioxide precursor solution having a samarium doping molar percentage of 3.75 mol%, and comprising the following steps: S1: preparing a precursor solution; specifically comprising the following sub-steps: S11: adding a hafnium salt to a solvent and stirring until it is completely dissolved; the added hafnium salt is C 20 H 28 HkDJ 8 ; S12: Add samarium salt and stir for more than 2 hours until a clear solution is obtained; the samarium salt added is Sm(NO 3 ) 3 •6H 2 O.
[0057] S11 and S21 are specifically as follows: weigh appropriate amounts of hafnium acetylacetonate and samarium nitrate hexahydrate and dissolve them in 3 ml of acetic acid to prepare a samarium-doped hafnium dioxide precursor solution. The concentration range of the precursor solution is 0.2 mol / L, wherein the doping molar percentage of samarium is 3.75 mol%. After all the solutes are dissolved, add an appropriate amount of acetylacetone solution, the volume ratio of the acetic acid solution to the acetylacetone solution is 2, adjust the pH value to 5 and make it have stable solution chemical properties, and after obtaining a light yellow clear solution, transfer the solution to a magnetic stirrer at 25°C and stir for 2 hours until a clear solution is obtained.
[0058] S13: After obtaining a clear solution, ageing in a dark environment for more than 72 hours to obtain a clear light yellow samarium-doped hafnium dioxide precursor solution.
[0059] S2: Clean the substrate. Pt(111) / TiN / SiO 2 / Si(100) substrate, the surface pretreatment method of the dried substrate is to use an ultraviolet ozone cleaning machine for 5 minutes.
[0060] When cleaning the substrate, first use deionized water for ultrasonic cleaning for 6 min, then use anhydrous ethanol for ultrasonic cleaning for 15 min, continue to use deionized water for ultrasonic cleaning for 6 min, then use acetone for ultrasonic cleaning for 15 min, and then use deionized water for ultrasonic cleaning for 6 min.
[0061] After each step of ultrasonic cleaning, rinse with a large amount of deionized water to remove impurities and dirt on the surface of the substrate to prevent stains from adhering to the surface of the substrate. Soak the substrate in anhydrous ethanol and dry it before use. Then pre-treat the surface of the dried substrate to increase the adsorption of the substrate surface to the precursor solution.
[0062] S3: coating and drying treatment; specifically, coating the precursor solution obtained in S1 on the substrate cleaned in S2, using a balloon to blow away surface impurities before coating, placing the substrate on a 180°C glue baking machine for drying for 5 minutes after each coating, then transferring the heated and dried substrate to a 400°C heating table for pyrolysis for 10 minutes, then cooling the dried and pyrolyzed film for 5 minutes, and then coating the next layer; repeating the above steps until the desired film thickness is prepared.
[0063] The coating process uses a spin coating process, and low-speed spin coating and high-speed spin coating are performed in sequence: Pt(111) / TiN / SiO 2 / Si(100) substrate is placed on a spin coater, and the precursor solution is dripped onto the surface of the substrate until it is fully covered. Then, it is first spun at a low speed of 600 r / min for 20 s, and then spun at a high speed of 5000 r / min for 45 s. Subsequently, it is placed in a glue baking machine and heated at 180 ° C for 5 min and 400 ° C for 10 min. The coating and drying steps can be repeated multiple times according to the film thickness requirements. The thickness of the single-layer samarium-doped hafnium dioxide film needs to be controlled to be 10~20 nm. In this embodiment, the above operation is repeated, and 4 layers are spin-coated to obtain a samarium-doped hafnium dioxide film with a film thickness of 80 nm.
[0064] S4: Preheating the film: Place the film obtained in S3 in an annealing furnace filled with protective gas for pre-annealing, then anneal, and cool to room temperature in the furnace to prepare a samarium-doped hafnium dioxide ferroelectric film. The specific method of annealing is: Place the substrate coated with the film in S3 in an annealing furnace for annealing. The annealing includes a pre-annealing process and a formal annealing process. The protective atmosphere is oxygen. The annealing process parameters are set as follows: Slowly heat from room temperature to 180 °C at a heating rate of 4 °C / s, keep for 3 min, and then heat to 300 °C at a heating rate of 15 °C / s, and keep for 3 min. Entering the formal annealing, during the formal annealing, the temperature is heated to 350°C at a heating rate of 15°C / s, maintained for 100s, and finally heated to 950°C at a heating rate of 40°C / s, maintained for 600s, and then cooled to room temperature with the furnace before being taken out. The gas in the furnace is one or more of oxygen, nitrogen, argon or air. In this embodiment, the gas in the furnace is nitrogen.
[0065] S5: The samarium-doped hafnium dioxide ferroelectric thin film prepared in S4 is plated with an electrode, wherein the electrode is an Au electrode.
[0066] Prepare a samarium-doped hafnium dioxide precursor solution with a samarium doping molar percentage of 3.75 mol% to obtain metal-Sm:HfO 2 Thin-film-metal (MIM) capacitors are tested for their ferroelectric properties using a ferroelectric analyzer and a semiconductor tester.
[0067] The sample was found to be a mixture of monoclinic and orthorhombic phases, with a residual polarization range of 9.24 to 13.46 μC / cm 2 , the coercive field range is 1.0-1.5 MV / cm. The hysteresis loop and transient current-field curve of the sample are shown in Figure 5 shown.
[0068] In the above embodiments, the hafnium dioxide films with different samarium doping concentrations all exhibit ferroelectricity, wherein when the molar percentage of samarium doping is 2.5 mol%, the hysteresis loop window is the largest and the best.
[0069] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a samarium-doped hafnium dioxide ferroelectric thin film having a high remanent polarization value, characterized in that: The steps include: S1: preparing a precursor solution; specifically comprising the following sub-steps: S11: adding hafnium salt to a solvent and stirring until all of it is dissolved; S12: adding samarium salt and stirring until a clear solution is obtained; S13: Aging in the dark to obtain a clear light yellow samarium-doped hafnium dioxide precursor solution; S2: cleaning the substrate; S3: coating and drying; specifically, coating the precursor solution obtained in S1 on the substrate cleaned in S2, removing surface impurities before coating; placing the substrate on a glue baking machine for drying after each coating, transferring the heated and dried substrate to a heating table for pyrolysis, cooling the dried and pyrolyzed film, and then coating the next layer; repeating the above steps until the desired film thickness is prepared; S4: Preheating the film: placing the film obtained in S3 in an annealing furnace filled with protective gas for pre-annealing, then annealing, and cooling to room temperature in the furnace to prepare a samarium-doped hafnium dioxide ferroelectric film; S5: Plate the samarium-doped hafnium dioxide ferroelectric thin film prepared in S4 onto an electrode.
2. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film having a high remanent polarization value according to claim 1, characterized in that: The hafnium salt added in S11 is C 20 H 28 HfO8; the samarium salt added to S12 is Sm(NO3)3•6H2O; the molar percentage of samarium ranges from 1 to 15 mol%.
3. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film having a high remanent polarization value according to claim 2, characterized in that: The molar percentage of samarium ranges from 1 to 5 mol%, preferably from 1.25 to 3.75 mol%.
4. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value according to claim 2, characterized in that: The concentration range of the samarium-doped hafnium dioxide precursor solution in S13 is 0.1-0.2 mol / L, preferably 0.1-0.15 mol / L.
5. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value according to claim 1, characterized in that: The solvent in S11 is a mixed solution of acetic acid solution and acetylacetone solution, wherein the volume ratio of acetic acid solution to acetylacetone solution is in the range of 1-2, and the pH of acetylacetone solution is adjusted to 3-5; when adding the solvent, the acetic acid solution should be added first, and after stirring, observe whether the solute is dissolved in the solvent, and then add the acetylacetone solution as a stabilizer.
6. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value according to claim 1, characterized in that: The substrate in S2 is a Pt(111) / TiN / SiO2 / Si(100) substrate; the surface pretreatment method of the dried substrate is to use an ultraviolet ozone cleaning machine.
7. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value according to claim 1, characterized in that: In S2, the substrate is cleaned by ultrasonic cleaning method. After each ultrasonic cleaning, water is used to rinse to remove impurities and dirt on the surface of the substrate. The substrate is soaked in anhydrous ethanol and dried before use. The dried substrate is then surface pretreated. When ultrasonic cleaning is performed, water ultrasonic cleaning is used for 4 to 6 minutes, anhydrous ethanol ultrasonic cleaning is used for 5 to 15 minutes, water ultrasonic cleaning is used for 4 to 6 minutes, acetone ultrasonic cleaning is used for 5 to 15 minutes, and water ultrasonic cleaning is used for 4 to 6 minutes.
8. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value according to claim 1, characterized in that: After each layer is coated in S3, the substrate needs to be placed on a 150~180 ℃ glue baking machine to dry for 3~5 minutes, and then the heated and dried substrate is transferred to a heating table at 300 ℃~400 ℃ for pyrolysis for 5~10 minutes, and then the dried and pyrolyzed film is cooled for 3~5 minutes before the next layer is coated.
9. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value according to claim 1, characterized in that: The coating method in S3 is spin coating, specifically, low-speed spin coating and high-speed spin coating are performed in sequence; the speed of low-speed spin coating is 300~600 r / min, and the time of low-speed spin coating is 10~20 s; the speed of high-speed spin coating is 3000~5000 r / min, and the time of high-speed spin coating is 25~45 s; the coating and drying treatment steps in S3 can be repeated multiple times according to the film thickness requirements, and the thickness of the single-layer samarium-doped hafnium dioxide film is controlled to be 10~20 nm.
10. The method for preparing a samarium-doped hafnium dioxide ferroelectric thin film with a high remanent polarization value according to claim 1, characterized in that: The process parameters of annealing in S4 are: heating from room temperature to 180~300 ℃ at a heating rate of 3~10 ℃ / s, then heating to 400~950 ℃ at a heating rate of 10~40 ℃ / s, keeping warm for 100~600 s, and then cooling to room temperature with the furnace; the gas in the furnace is one or more of oxygen, nitrogen, argon or air.
Citation Information
Patent Citations
Lanthanum-doped hafnium oxide ferroelectric film preparation method and application
CN110648902A
Semiconductor oxide thin film, preparation method thereof and thin film transistor comprising semiconductor oxide thin film
CN110690107A
Rare earth doped hafnium dioxide-based ferroelectric film and preparation method thereof
CN112176315A
Preparation method and application of cerium-doped hafnium zirconium oxide ferroelectric film with high remanent polarization
CN115020210A
Co-doped hafnium oxide-based ferroelectric film and preparation method thereof
CN118610198A